Assessment of Water Quality of Bokor River, Surabaya City as an Effort to Support the Sustainability of Fish Pond Business in the Downstream - Moh Rizal Ngambah Sagara; I Wayan Koko Suryawan; Iva Yenis Septiariva (Journal of Sustainable Infrastructure, 2022)
Due to human activities, both domestic and non-domestic, river pollution can occur over time. One of the rivers in Surabaya, which is located in a densely populated area, is Bokor River. Residents use Bokor River for pond activities, so the water's quality must meet these quality standards. This study aims to analyze the suitability of river water quality in Bokor River, Surabaya City, which has met its quality standards for this activity. Water quality measurement is carried out by existing testing with the standard method that is used as a reference in Indonesia. Water quality measurements were determined based on the parameters BOD, COD, DO, TSS, Phosphate (PO4 3-), Nitrate (NO3), and Ammonium (NH4). The measured DO, BOD, phosphate, and ammonia parameters did not meet these quality standards. However, DO parameters in the upstream still meet the quality standard (above 3 mg/L), while after that, they experience a decrease in quality. Meanwhile, nutrient parameters, especially ammonia, do not meet quality standards, as it is known that ammonia can provide toxic properties to fish. In addition, there is an opportunity for eutrophication of this quality. Pollutants entering the Bokor River are point sources and non-point sources, which cannot be located precisely and generally consist of many relatively small individual sources.